IDENTIFICATION OF THE MICROBIOLOGICAL RISKS OF CONTAMINATION OF CATTLE AND PIG CARCASSES WITH PATHOGENS AT SLAUGHTER AND PROCESSING - D. S. Bataeva; Yu. K. Yushina; E. V. Zaiko (Теория и практика переработки мяса)
In this work, the risk of contamination of cattle and pig carcasses with pathogens at different stages of their slaughter and processing was assessed. The analysis of meat (carcasses, half carcasses and cuts) and meat semi-prepared products from beef and pork for the presence of the microorganisms of the genera Salmonella and Listeria, and Listeria monocytogenes in the samples taken by the destructive (from the depth) and nondestructive (from the surface) methods was carried out to determine the critical points. It was found that the deep layers of beef and pork cuts were not contaminated with the microorganisms of the genus Salmonella and L.monocytogenes. However, surface contamination of cattle and pig carcasses and half-carcasses with Salmonella and L.monocytogenes was revealed at the stages of hide removal and evisceration of the carcasses. Dry and wet cleaning of carcasses and half-carcasses did not facilitate the reduction of contamination. This fact is the cause of contamination of meat semi-prepared products (small-sized and minced), which was established during the study.